Selection and Validation of Stable Reference Genes for RT-qPCR in Scotogramma trifolii (Lepidoptera: Noctuidae) - Anpei Yang; Hang Zhang; Weiwei Bai; Ruifeng Ding; Weipeng Li; Guangkuo Li (Insects)
The clover cutworm, Scotogramma trifolii Rottemberg (Lepidoptera: Noctuidae), is a globally distributed polyphagous pest causing significant economic losses to agricultural crops. RT-qPCR is a gold-standard technique for gene expression analysis, yet its accuracy depends critically on stable reference genes for data normalization. To address the lack of validated reference genes in S. trifolii, we evaluated six candidate genes (β-actin, RPL9, GAPDH, RPL10, EF1-α, and TUB) across four developmental stages (egg, larva, pupa, and adult) and six adult tissues (head, thorax, abdomen, wings, legs, and antennae) using geNorm, NormFinder, BestKeeper, and RefFinder algorithms. Stability analysis identified β-actin, RPL9, and GAPDH as the most reliable reference genes for developmental stage normalization, while RPL10, GAPDH, and TUB were validated for adult tissues. Functional validation using the odorant receptor gene StriOR20 revealed significant discrepancies in relative expression levels when normalized with unstable reference genes (TUB and RPL9), emphasizing the necessity of rigorous reference gene selection. This study establishes the first comprehensive reference gene panel for S. trifolii, providing a robust foundation for gene expression studies in this agriculturally important pest.